Studies on the Improvement of the Nutritive Value and Utilization of Palm Kernel Cake as a Feed Resource for Ruminants - Chinajariyawong, Charurat (2000)
Utilization of palm kernel cake (PKC) as the principal feed for ruminants was investigated in four studies. The study on the nutritive value showed that PKC·solvent extracted (PKC·S) and PKC·expeller pressed (PKC·E) contained similar amounts of OM, CP, CF and ADL. PKC·E had higher OM. EE and GE but lower NFE, NDF. ADF and shell contents. Amounts of Ca. P. Cu and Zn were similar in both types ofPKC, but Na was higher and Mg was lower in PKCS. Ruminal pH. NH3-N concentration. molar proportions of YF A and passage rates of liquid and small digesta particles in cattle fed either PKC·S or PKC·E were similar. Total YF A concentration was higher in cattle fed PKC·S. Effective OM and OM degradabilities were lower in animals fed PKC-S. but degradatIOn rates were similar. PKC-E contained more soluble fractions than PKC-S. CP of PKC-S was more soluble. but its effective degradability and degradation rate were similar to that of PKC-E. The study on the effects of formaldehyde treatments on CP degradability of both types of PKC showed that CP degradability decreased with increasing levels of formaldehyde. Acid-pepsin digestibility showed no difference in CP digestibility among untreated and formaldehyde-treated PKC up to 2.5g/l OOg CP. The study on the effects of PKC and formaldehyde treatment on the performance and nutrient utilization of cattle showed that feed intake was lower in cattle fed PKC-E, but growth rates and feed per gain ratios did not differ from those fed PKC-S. Formaldehyde-treated (2g/100g CP) PKC gave poorer growth rates and feed conversion ratios when compared to untreated PKC. Types of PKC and formaldehyde treatment did not affect the nutrient digestibility. but PKC-E gave lower N retention. Formaldehyde had no effect on N retention. In the final study, lambs fed PKC + 15% grass showed improvement in intakes and growth rates. Urea at either 0.5 or 1.0%. had no effect on feed intakes and feed conversion ratios. However. growth rates of lambs fed PKC + 0.5% urea were higher compared to other groups. Lambs fed PKC plus 15% grass and 0.5% urea had the highest intake and growth rate. Carcass traits were not affected by urea but grass supplementation reduced dressing percent and kidney fat of lambs